Global health research abstracts: November ‘24 - Dr. Jonathan Kajjimu (African Journal of Emergency Medicine)
The African Journal of Emergency Medicine, in partnership with several other regional emergency medicine journals, publishes abstracts from each respective journal. Abstracts are not necessarily linked to open access papers however, all abstracts are accessible without subscription.